Lirmasetad Learning Media (Linktree Regional Dance Arts Materials) In Primary School SBdP Lesson Content - Kurniawan, Ragil; Ary, Deasylina da (JETL (Journal of Education, Teaching and Learning), 2024)
Elementary School Purwoyoso 04 is experiencing problems regarding the lack of use of digital-based learning media and less than optimal learning outcomes in art lesson content. The problem formulation in the research describes how to develop, test the feasibility, and test the effectiveness of LIRMASETAD Learning media. This research procedure uses ten stages of sugiono development. Development was done using Canva web design, which was then integrated into Linktree. This development research aims to determine the application of learning media and the feasibility and effectiveness of LIRMASETAD learning media. The research results show that LIRMASETAD Learning is suitable for understanding with a presentation feasibility percentage by media experts of 88% and the feasibility of teaching components by material experts of 90.6%. The effectiveness of the media is demonstrated through normality test results. Based on calculations, a sig value of 0.165 is obtained, assuming that if the sig value is >0.05, the data is normally distributed. Based on the results of the n-gain test, the cognitive n-gain score was 0.63, with an average difference of 33.2. So, the n-gain value on cognitive pretest and posttest learning outcomes in large group use trials is in the high category, with an effectiveness level of 63,557, which is quite effective. The increase in average shows that learning using LIRMASETAD media is effective as a learning medium. Suggestions for further research include applying media to more diverse material to be used in other learning processes.